2015
DOI: 10.15252/embj.201591125
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of synaptic activity by snapin‐mediated endolysosomal transport and sorting

Abstract: Recycling synaptic vesicles (SVs) transit through early endosomal sorting stations, which raises a fundamental question: are SVs sorted toward endolysosomal pathways? Here, we used snapin mutants as tools to assess how endolysosomal sorting and trafficking impact presynaptic activity in wild-type and snapin À/À neurons. Snapin acts as a dynein adaptor that mediates the retrograde transport of late endosomes (LEs) and interacts with dysbindin, a subunit of the endosomal sorting complex BLOC-1. Expressing dynein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 96 publications
(157 reference statements)
2
37
0
1
Order By: Relevance
“…In Snapin knockout mice, synaptic late endosomes are defective [28]. The authors showed that Snapin directly interacts with dynein intermediate chain and suggested that Snapin activates the retrograde transport of synaptic endosomes [29].…”
Section: Discussionmentioning
confidence: 99%
“…In Snapin knockout mice, synaptic late endosomes are defective [28]. The authors showed that Snapin directly interacts with dynein intermediate chain and suggested that Snapin activates the retrograde transport of synaptic endosomes [29].…”
Section: Discussionmentioning
confidence: 99%
“…12 In contrast, in neurons, the speed of retrograde delivery of endosomes from peripheral axons to the central soma is reduced, potentially impairing endosome-lysosome fusion. 12,13 RAB7 is necessary for endosome-lysosome fusion, 67 and in macrophages, RAB7 levels are not changed in SNAPIN-silenced macrophages, suggesting no increase of late endosome accumulation. Additionally, depletion of RAB7 in HeLa cells impairs cargo transfer from endosomes to the lysosomes, suggesting RAB7 is required for endosome-to-lysosome delivery.…”
Section: Ctse (Cathepsin E)mentioning
confidence: 97%
“…In neurons, BLOC‐1 is implicated in the biogenesis and release of synaptic vesicles in presynaptic terminals (Newell‐Litwa et al . ; Di Giovanni and Sheng ; Chen et al ., ). In addition, neurons from pallid mutant mice show impaired neurite outgrowth (Ghiani et al .…”
Section: Summary Of Cytohesin‐interacting Moleculesmentioning
confidence: 99%